Can Placement of Governmental Sector Jobs Spur Private Sector Employment and Performance? - Harald Dale-Olsen; Pal Schone (Institute of Labor Economics (IZA), 2020)
We analyse the impact of establishment of governmental sector jobs on private sector employment based on Norwegian population-wide administrative-register data. Based on precise geographical information on the location of jobs, differential treatment intensities yield identification of causal effects. The results suggest that governmental employment has positive effects on private sector employment in the close proximity of the stimulus area. In the same area, we also observe positive short-term effects on wage growth and on firms' sales. Over time, only employment effects prevail. Two different types of placebo tests give support to the causal interpretation of the main results.
Keywords: J61; R23; 330; regional labour markets; central government jobs; job creation